Assessing the Effectiveness of Intellectual Property Law Enforcement in Indonesia: Legal Substance, Institutional Structure, and Legal Culture - Pajrin, Rani; Saputra, Rian; Kurniawan, Itok Dwi (Kosmik Hukum, 2026)
This article examines the effectiveness of intellectual property rights law enforcement in Indonesia by analysing three main elements of the legal system: legal substance, legal structure, and legal culture. The study focuses on the enforcement of intellectual property rights through civil mechanisms, criminal proceedings, and alternative dispute resolution. The analysis shows that the effectiveness of intellectual property enforcement is influenced not only by the adequacy of legal norms, but also by the capacity and coordination of law enforcement institutions, procedural efficiency, and public legal awareness. In civil disputes, parties are encouraged to strengthen contractual clauses that refer disputes to alternative dispute resolution or arbitration mechanisms, as these forums may provide faster, more confidential, cost-efficient, and legally certain outcomes. Meanwhile, in criminal enforcement, challenges remain in the technical capacity of law enforcement officials, inter-institutional coordination, and bureaucratic complexity. Therefore, improving intellectual property law enforcement in Indonesia requires strengthening the competence of law enforcement officers, simplifying enforcement procedures, enhancing institutional collaboration, and increasing public awareness of intellectual property protection. These measures are essential to create a more professional, efficient, and practical enforcement system that supports legal certainty and the protection of innovation.